School prevention of non-consensual sexting among middle adolescents: Does sexual preoccupation awareness matter? - Touloupis, Thanos (Frontiers in Psychology, 2024)
Although non-consensual sexting seems to concern not only adults but also middle adolescent students, with detrimental consequences on their well-being, the related research-based effective school prevention programs are almost absent. Furthermore, there is an unanswered research question as to whether sex-related issues, such as sexual preoccupation, matters in adolescents’ non-consensual sexting and its prevention. The present study investigated the effectiveness of a school-based intervention against non-consensual sexting among middle adolescents, based on the European funded program TABBY (Threat Assessment of Bullying Behavior in Youth). Furthermore, the predictive role of sexual preoccupation was examined. Overall, 280 Greek students from randomly selected junior high school responded to self-report scales on non-consensual sexting and sexual preoccupation. Based on an experimental longitudinal research design, only the experimental (N = 131), but not the control group of students (N = 149), participated in the intervention. To test the effectiveness of the intervention, both student groups completed the scales before (1st phase), immediately after (2nd phase), and six months after the intervention (3rd phase), which was implemented by trained teachers. The results showed both, the short-term and long-term effectiveness of the intervention. Also, the study highlighted the significant contribution of sexual preoccupation awareness in reducing non-consensual sexting, especially immediately after and six months after the intervention. The study implies the necessity to adapt existed prevention programs to the specific parameters of non-consensual sexting, integrating at the same time sexual preoccupation awareness activities to better address this issue.